Respostas
respondido por:
2
an=a1+(n-1).r
112=2+(n-1).11
112=2+11n-11
-11n=2-11-112
-11n=-121 só que n nao pode ser negativo entao vc multiplica toda a conta por -1
11n=121
n=121 dividido por 11
n=11
112=2+(n-1).11
112=2+11n-11
-11n=2-11-112
-11n=-121 só que n nao pode ser negativo entao vc multiplica toda a conta por -1
11n=121
n=121 dividido por 11
n=11
respondido por:
0
resolução!
an = a1 + ( n - 1 ) r
112 = 2 + ( n - 1 ) 11
112 = 2 + 11n - 11
112 = - 9 + 11n
112 + 9 = 11n
121 = 11n
n = 121 / 11
n = 11
resposta: PA de 11 termos
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás